Anterior cruciate ligament injuries in the female athlete - Baker, M. M. (Journal of Women's Health, 1998)
The normal anterior cruciate ligament (ACL) is critical to knee joint stability, especially for athletes in cutting sports. Rupture of the ACL can be a devastating, if not career-ending, injury for a young athlete because of the resultant instability and increased risk of meniscal and chondral damage. Considerably more girls and women than ever before now participate in athletics. Some epidemiologic data show that female athletes may sustain a higher incidence of ACL injuries than male athletes. Risk factors that may be responsible for these increased injury rates are reviewed. History and physical examination are most important in establishing the diagnosis of ACL injury, although ancillary diagnostic imaging is helpful if the extent of injury is in question. Treatment options, including various surgical reconstructions and rehabilitation, are discussed, with attention to the specific concerns of the female athlete. With appropriate diagnosis and treatment, the ACL-injured athlete may now anticipate full return to function and athletic competition.